Promoting Competition in the Distribution of Mutual Funds : Lessons for Securities Markets Regulatory Authorities in Emerging Market Economies - World Bank Group (World Bank, Washington, DC, 2018)
This Policy Note focuses on distribution channels, the role they play in product diversification and costs, and how regulation can promote competition in mutual funds (MFs) distribution. In many emerging market economics (EMEs) where both the capital markets and the MFs have reached certain level of development, distribution channels are dominated by banks and their groups. This dominance in turn allows them to keep a "closed architecture" and to offer their clients only the products they manufacture. However, different forces are opening the doors to competition in the distribution channels including (i) a higher level of development of the MF industry, anchored in a growing middle class with additional savings to invest; (ii) financial innovation, which has been supported by demographics and the increased penetration of internet, social media and mobile services; and (iii) regulatory reforms, some of them explicitly aimed at increasing competition. These forces are driving the emergence of new distribution channels, particularly but not exclusively in the form of electronic platforms which might enable retail investors to access a wider variety of products, potentially at lower costs, and robo-advisors, which can lower the costs of accessing advice, potentially enabling retail investors to be better informed.